ANALISIS PENGELOLAAN PAJAK BUMI DAN BANGUNAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - Agus Riyanto; Martinus Robert Hutauruk; Novita Dewi (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to determine the management of PBB(Land and Building Tax) in increasing local revenue in Samarinda City. The research method uses qualitative research methods with data collection techniques in the form of interviews with the Head of the Samarinda City Bapenda. The results of this research are that the management of PBB in the city of Samarinda includes the management of socialization regarding PBB through events as well as the application of information technology in the form of smart PBB. Meanwhile, the factors that influence the management of PBB in the City of Samarinda are Taxpayer Compliance and the application of information and communication technology in the form of smart PBB